(untitled) (Research, Society and Development, 2024)
Project management has undergone gradual evolution through the consolidation of various practices available in the whole world, whether they are accessible virtually or disseminated in an applied way and exemplified in the launch of new products. However, consolidating project management with the execution of activities, covering all necessary dimensions, becomes challenging for the vast majority of managers. On this base, this research is a field study carried out in a multinational company with the objective of evaluating the use of knowledge and skills of participants in the project management team, through the use of the Herrmann Brain Dominance Instrument Profile - HBDI, with which, depending on the choice of the members, it is possible to make project management performance more productive and with predictable results, associated with the application of a technical quality manual that helps team participants to complete all essential phases during the implementation of a new project.